PANCASILA-BASED DIGITAL FLASHCARD FOR ELEMENTARY STUDENTS - Tri Arie Bowo; Yoannes Romando Sipayung; Budiati Budiati (p-ISSN 2356-0576, 2021)
This study aims to research and develop instructional media so that it can improve elementary school students' English vocabulary, especially vocabulary related to Pancasila values. The specific objective of this research is to determine the results of knowledge attainment using Pancasila-based digital flashcard application media and conventional media. The novelty of this research is to use the Pancasila values variable in improving English vocabulary. Research and Development method is used in this research consisting of product manufacturing, initial product validation, product testing, usage trials, and final product. This research produces Pancasila-based Digital Flashcard for Elementary Students which contains several users’ interface pages, namely the home page, question page, answer page, and scoring page. It also has several function buttons, namely the exit button, home button, previous button, and next button. Based on the effectiveness test, Pancasila-based Digital Flashcard for Elementary Students is more effective compared to conventional flashcard in achieving vocabularies related to Pancasila values. Further research can be carried out related to interactive learning media, especially in an effort to improve the nation's character building.